Perubahan Fonologis Kata Serapan Bahasa Arab dalam Istilah Keagamaan di Indonesia / Phonological Changes in Arabic Loan Words in Religious Terms in Indonesia - Khairudin Khairudin; Khaerunnisa Nuur; Hamzah Hamzah; Muh Nur Abduh (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2024)
This research aims to determine the process of phonological changes in Arabic loan words into Indonesian, and the types of phonological changes that occur in Arabic loan words. The research method used in this research is a descriptive qualitative research method. This type of research includes literature study or content analysis, which analyzes in detail the phonological changes in Arabic loan words that have entered Indonesian. The results of this research were that the letters that experienced phonological changes were letters that the Indonesian language did not have, so letters were chosen whose pronunciation was similar or close to the letters in the Indonesian language. This also shows that there have been many changes in Arabic loan words into Indonesian. This change occurs in the position of consonants and vowels. Apart from that, there are many changes in one word which researchers term as double changes, in one word sometimes there is one change, two or even three changes as happens in the words aqi>dah and istiqa>mah. There are also several letters that are owned by Arabic which are also owned by Indonesian but are still undergoing changes, such as words that sound /q/. In general, the sound /q/ undergoes a phonological change process to become /k/ when it becomes a loan word, but there is also a sound /q/ in Arabic that does not undergo phonological change when it becomes a loan word, namely as in the word